HIV anti-stigma toolkit for faith-based organisations (CARICOM Secretariat GeorgetownGY, 2009)
Aims to assist religious leaders and key decision-makers as well as members within faith-based organisations to provide guidance, support and care to all People Living with HIV (PLHIV).
Keywords: HIV